PERBEDAAN EFEKTIVITAS CONSTRUCTED WETLANDS RECIRCULATING FREE WATER SURFACE DAN SUBSURFACE FLOW SYSTEM ECHINODORUS PALAEFOLIUS UNTUK MENURUNKAN FOSFAT LIMBAH CAIR RUMAH TANGGA (GREYWATER) Studi Kasus : Kelurahan Gedawang, Kecamatan Banyumanik, - Shofa Rakhmatika; Tri Joko; Nurjazuli Nurjazuli (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Domestic wastewater was one source of water pollution potential. Constructed wetlands system is recognized as one of the technologies that can be used in conjunction with traditional wastewater treatment technology as a cost effective waste water management options in both developed and developing countries. The purpose of this study was to determine differences in the effectiveness of constructed wetlands system of continuous type Free Water Surface and Subsurface Flow System to removal levels of phosphate in domestic wastewater (greywater) in the sub Gedawang, Banyumanik subdistrict, Semarang. This research was a quasi experimental research with nonrandomized pretest posttest design. Processing using constructed wetlands with a residence time of 5 days with 16 repetitions. The results showed a decrease in the average efficiency of phosphate to the type of Free Water Surface and Subsurface Flow System, respectively 69.07% and 71.86%. Independent T -Test results different from test obtained p-value 0.876 (p value> 0.05) showed no difference in phosphate levels decrease the effectiveness of domestic wastewater (gray water). It was concluded that the phosphate content is appropriate quality standards, but the method of Free Water Surface and Subsurface Flow System did not show a difference. Further research is needed with a variety of other plant species, variation of media, and variations in residence time.